FAKTOR - FAKTOR YANG MEMPENGARUHI TANGGUNG JAWAB AUDITOR DALAM MENDETEKSI KECURANGAN LAPORAN KEUANGAN (Studi Empiris Pada Kantor Akuntan Publik Di Semarang) - Retno Widhiyaningrum, 12.05.52.0209; Setyowati, Widhy (Students Journal of Accounting and Banking, 2016)
This study aimed to examine the effect of the independence, competence, experience, knowledge and professional skepticism to the responsibilities of the auditor in detecting fraudulent financial statements. This research was conducted on a public accounting firm in the area of Semarang. The population in this study are all auditors who are in the public accounting firm in the area of Semarang. Sampling using convenience sampling method. Primary data collection method used is the questionnaire with the data analysis using multiple linear regression model. The results showed that the experience and knowledge not affect the responsibilities of the auditor in detecting fraudulent financial statements, while the independence, competence and professional skepticism significant positive effect on the auditors responsibility to detect fraud in the financial statements.Keywords: Independence, Competence, Experience, Knowledge, Professional Skepticism And Responsibilities Of The Auditor In Detecting Fraudulent Financial Statements